2012
DOI: 10.1161/atvbaha.111.242792
|View full text |Cite
|
Sign up to set email alerts
|

EphA2 Activation Promotes the Endothelial Cell Inflammatory Response

Abstract: Objective Endothelial cell activation results in altered cell-cell interactions with adjacent endothelial cells and with infiltrating leukocytes. Eph receptors and their ephrin ligands regulate cell-cell interactions during tissue remodeling, and multiple proinflammatory mediators induce endothelial EphA receptor and ephrinA ligand expression. Therefore, we sought to elucidate the role of EphA receptors and ephrinA ligands in endothelial cell activation and atherosclerosis. Methods and Results qRT-PCR screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 51 publications
4
78
0
Order By: Relevance
“…Although originally identified as regulators of axon guidance, the Eph receptors are now known to play profound roles in diverse physiological processes, such as angiogenesis (formation of new blood vessels from pre-existing ones), bone morphogenesis, inflammatory host responses, neurodegenerative diseases, and cancer (2,3). The Eph receptors are unique among the RTKs, as their mechanism of activation is distinctly different and much more complex.…”
mentioning
confidence: 99%
“…Although originally identified as regulators of axon guidance, the Eph receptors are now known to play profound roles in diverse physiological processes, such as angiogenesis (formation of new blood vessels from pre-existing ones), bone morphogenesis, inflammatory host responses, neurodegenerative diseases, and cancer (2,3). The Eph receptors are unique among the RTKs, as their mechanism of activation is distinctly different and much more complex.…”
mentioning
confidence: 99%
“…Human normal and atherosclerotic artery specimen: All human normal and atherosclerotic artery samples were collected as described previously following the protocols approved by the Institutional Review Boards (37). These samples were considered to be deemed nonhuman subjects, as they were postmortem samples.…”
Section: Methodsmentioning
confidence: 99%
“…Endothelial activation with oxidized low-density lipoprotein and proinflammatory cytokines resulted in induction of EphA2 and EphA1 with sustained EphA2 activation. This resulted in proinflammatory gene expression and VCAM-1 and E-selectin induction, and identified these ephrins as potential regulators of atherosclerotic plaque development [86]. Van Gils et al showed that EphB2 is upregulated under proatherosclerotic flow conditions and functions as a chemoattractant, increasing leukocyte migration in the absence of additional chemokines [83].…”
Section: Neuronal Guidance Proteins In Atherosclerosismentioning
confidence: 99%